The undamaged tissue grasping in a laparoscopic surgical grasper via distributed pressure measurement - Sümer, Bilsay; Özin, Mithat Can; Eray, Turgay; Koç, İlker Murat (Elsevier BV, 2017)
Abstract The grasping action in a minimally invasive surgery operation is a blind operation in terms of the touch feedback and may result an undesirable tissue damage during the surgery. In this study, the interaction of the minimally invasive surgery tool with the tissue investigated by integrating a high resolution tactile sensor to the end-effector of the tool. The pressure distribution during the closing action of the grasper is characterized using the non-organic viscoelastic materials as well as organic tissues such as dead chicken liver and meat. Pressure mapping is used to calculate the net grasping force acting on the contact interface. The results show the total grasping force changes in the range of 0.2–0.7 N for different types of tissues.